Salvage - Norton, Roy, 1869-1942 (Salt Lake City, UT : Project Gutenberg, 2024)
"Salvage" by Roy Norton is a novel written in the early 20th century. The story centers around Captain Eli Drake, an independent shipowner navigating the challenging waters of the shipping industry during a time of economic downturn. The narrative unfolds in the historic port of Piræus, Greece, where Captain Drake seeks opportunities amidst his financial struggles and the prevalence of larger steamship companies driving independent merchants out of business. The plot follows Captain Drake as he discovers a suspicious ship, the Rhodialim, seemingly on the verge of being scuttled by its captain, Bill Morris. With the help of his dedicated crew and a resourceful new engineer, Giuseppe Beltramo, Drake concocts a plan to salvage the ship and thwart the nefarious intentions of its crew. This adventure pits scattered elements of deception against loyalty and survival, with Drake leveraging both strategy and brute force to secure the salvage against a backdrop of treachery at sea. In the end, Captain Drake emerges victorious, not only saving the Rhodialim but also planning to use the salvage money to reward his loyal crew. (This is an automatically generated summary.)
Release date is 2024-03-24
Roger Frank and Sue Clark
Keywords: Short stories; Sea stories; Ship captains -- Fiction